Optimization of the Role of Dai Kamtibmas by the Binmas Unit of Kuningan Police to Prevent Conflict Between Mass Organizations in the Order of Maintaining Kamtibmas - Syakhranie, Akhmad Abiyardie (Indonesian Journal of Police Studies, 2024)
Phenomena that occur in society today, with increasing knowledge can affect the way of thinking, and acting on the community that have an impact on crime, for example is a conflict between community organizations. One example of conflict between community organizations that are rife in Indonesia is the case of differences in belief. Binmas serves to prevent and resolve problems by prioritizing communication by engaging in a psychological approach that is persuasive in nature, efforts by the Binmas Unit to get closer to the community must be optimized.The purpose of this study is to describe the empowerment of communication with religious leaders and the implementation of Model B 54 Community Policing as a media for preventing conflict between mass organizations by the Kuningan Police Binmas unit.This study uses a qualitative approach to the type of descriptive analysis research. The location of this research took place at Kuningan Police. Data collection techniques using interviews, observation and document studies. The validity of the data used in this study uses convergability, transformability and triangulation.The results of this study revealed that the Polri promoter program carried out reforms in two fields, namely the field of guidance and in the operational field were analyzed using management theory (POAC) carried out by the Kuningan Police Binmas unit. External factors that influence the implementation of the Binmas unit are many members of Dai Kamtibmas who are not really community leaders who cause the task of the Binmas unit and the community to be neglected while the internal factors that influence are the members’ infrastructure is still lacking, where members of the binmas unit still use private vehicles.